PENGARUH POTENSI DIRI, PERENCANAAN KARIR, PRESTASI BELAJAR, DAN DUKUNGAN ORANG TUA TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DI SMAN 2 GUNUNG TALANG - Inggritia Sarnila Putri; Indra Mulia Pratama; Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of self-potential, career planning, learning achievement, and parental support on students' interest in continuing their education to higher education at SMAN 2 Gunung Talang. This research uses a quantitative approach with associative descriptive methods. The population consists of 155 students of grade XI, and the sample of 111 students was obtained using the Slovin formula with random sampling technique. The data analysis technique used multiple linear regression with Eviews12 software. The results showed that self-potential, career planning, learning achievement, and parental support partially had a significant effect on students’ interest, except learning achievement which had a weaker influence. Simultaneously, all variables significantly affected students’ interest in continuing to higher education. This research highlights the importance of strengthening students’ self-potential, career planning, and parental involvement to increase their interest in pursuing higher education.